2004
DOI: 10.1103/physrevlett.93.186001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Swimming at Low Reynolds Numbers

Abstract: Efficient swimming at low Reynolds numbers is a major concern of microbots. To compare the efficiencies of different swimmers we introduce the notion of "a swimming drag coefficient" which allows for the ranking of swimmers. We find the optimal swimmer within a certain class of two-dimensional swimmers using conformal mapping techniques.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 22 publications
4
153
0
Order By: Relevance
“…They are thus very expedient to use for synthetic nanomotors whose mechanical degrees of freedom are hard to control. In contrast to the efficiency of molecular motors [10] or other swimming mechanisms at low Reynolds numbers [11][12][13], the efficiency of surface-driven propulsion has, to our knowledge, received no attention so far. However, this question becomes relevant when energy resources are limited by the environment of the swimmer.…”
mentioning
confidence: 96%
“…They are thus very expedient to use for synthetic nanomotors whose mechanical degrees of freedom are hard to control. In contrast to the efficiency of molecular motors [10] or other swimming mechanisms at low Reynolds numbers [11][12][13], the efficiency of surface-driven propulsion has, to our knowledge, received no attention so far. However, this question becomes relevant when energy resources are limited by the environment of the swimmer.…”
mentioning
confidence: 96%
“…In dimensions D > 2 the translational part of the gauge potential can be determined by the condition that the net force on the swimmer vanish. In two dimensions, however, the net force vanishes identically [24] and so one must instead determine the translational part of the gauge potential by requiring that the fluid velocity vanish at infinity [25]. We discuss this condition in more detail in Section V.…”
Section: Equations Of Motion Force and Torquementioning
confidence: 99%
“…The swimmer feels no net force (a generic result for Stokes flows in two dimensions [24]) and the total torque is…”
Section: Equations Of Motion Force and Torquementioning
confidence: 99%
“…Recent technical advances have led to ever more precise fabrication at small scales (microns or less), prompting both theorists [9][10][11][12][13] and experimentalists [14] to design and analyze a series of simple low-Reynolds number swimmers. The experiment of Dreyfus et al [14], in particular, reported locomotion in a sperm-like micro-swimmer, composed of a cargo (red blood cell) and a slender flexible filament made of a series of paramagnetic beads.…”
Section: Introductionmentioning
confidence: 99%